(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article delves into the concept of “literary concept” as a cognitive unit that emerges within an author’s conceptual field, shaped by both national and individual factors. It explores how literary concepts are rooted in the author’s worldview and their cultural or national identity, as well as how they can be expanded through unique linguistic means, stylistic devices, and personal semantic systems. The article emphasizes the role of literary concepts in poetic texts, illustrating how they reflect the author’s emotional state and worldview while also generating new meanings through their interaction with readers. Additionally, the paper examines the concept of idiostyle, which represents the author’s personal semantic system in literary works, and highlights the complexity of stylistic devices in revealing the author’s individuality. Through an analysis of the poems “Orol” by Abdulla Oripov and Muhammad Yusuf, the article demonstrates how literary concepts can transcend their literal meanings, conveying profound emotional and conceptual significance. The study also touches on cognitive and stylistic perspectives in the analysis of literary texts, underscoring the importance of stylistic devices in shaping the clarity and depth of conceptual meanings in literature. This research contributes to the understanding of how linguistic and stylistic tools interact to construct complex meanings and reflect both individual and cultural identities within literary works, offering insights into the evolving field of cognitive stylistics.